Hubungan Intensitas Penyemprotan Pestisida dengan Kadar Kolinesterase dalam Darah Petani di Desa Pasirhalang Kabupaten Bandung Barat - Gita Nur Fajriani (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2019)
Background: The intensity of pesticide spraying is how often farmers spray pesticides in one week. The more often farmers spray, the higher the risk of poisoning. The number of farmers who spray pesticides more than twice a week is caused by disturbances from plant disturbing organisms (OPT). This pest causes a lot of losses to farmers, such as damage to crops, causing losses to harvest crops.Aim: This research tried to investigate significant correlation between intensity of pesticide spraying with cholinesterase levels on farmer’s blood in Desa Pasirhalang Kabupaten Bandung Barat.Method: The research was analytical research and conducted with a cross sectional analytical survey conducted.Result: The results of the statistical test using SPSS with the chi-square test obtained asymptotic significance (2-sided) value is 0.107 greater than the alpha value (0.05). This shows that there is no significant correlation between the intensity of spraying pesticides with cholinesterase levels in the blood of farmers in Pasirhalang Village West Bandung Regency.Conclusion: Based on the test results, it is concluded that there is no significant correlation between the intensity of spraying pesticides with the level of cholinesterase in the blood of farmers in Desa Pasirhalang Kabupaten Bandung Barat.